(untitled) («СОВРЕМЕННЫЕ ФИЛОЛОГИЧЕСКИЕ ПАРАДИГМЫ: ВЗАИМОДЕЙСТВИЕ ТРАДИЦИЙ И ИННОВАЦИЙ», 2025)
The main purpose of this article is to explain the basic elements of the modern psycholinguistic approach to the study of text. As a result, two primary activities must be completed: 1) To list the characteristics that set this method apart from the linguistic approach; 2) To give a summary of the literature on how these perspectives are used to perceive and interpret the text. We’ll talk about the psycholinguistic definition of text, how speech messages are seen in patterns, and components that help with appropriate text interpretation. All of this is done to complete the assigned responsibilities.